Behçet’s Disease: an Insight from a Cardiologist’s Point of View - Cocco, Giuseppe (Bentham Open, 2010)
Behçet's disease (BD) is an enigmatic inflammatory disorder, with vasculitis (perivasculitis) underlying pathophysiology of its multisystemic affections. Venous pathology and thrombotic complications are hallmarks of BD. However, it has been increasingly recognized that cardiac involvement and arterial complications (aneurysms, pseudoaneurysms, rupture and thrombosis) are important part of the course of BD. Pericarditis, myocardial (diastolic and/or systolic dysfunction), valvular and coronary (thrombosis, aneurysms, rupture) involvement, intracardiac thrombi (predominantly right-sided) are, probably, the most frequent cardiac manifestations. Treatment of cardiovascular involvement in BD is largely empirical and aimed at suppression of vasculitis. The most challenging seems to be the treatment of arterial aneurysms and thromboses due to the associated risk of bleedings. Cardiologists should always bear in mind potential threats of (a)symptomatic cardiovascular involvement in BD.